Reducing the adverse effects of blasting on the cave ecosystem near the future exploitation field Gradusa (Rudarsko-geološko-naftni zbornik, 2018)
The future exploitation field of technical-construction stone Gradusa is located in the area of Sunja municipality in Sisak-Moslavina County. Near Gradusa there is a cave that is part of the ecological network as a conservation area important for several species and habitat types of bats. The significance of the cave is also its location in the continental part of Croatia where it is among a small number of objects that bats can use in all periods of their annual cycle. Due to the location and importance of habitats, there was a need to define the primary environmental impacts assessment for the ecological network. This assessment is the most important document for the possible acquiring of a location permit for exploitation from the future quarry of Gradusa. This paper presents the results of trial blasting and guidelines for reducing the adverse blasting effects on the cave ecosystem near future exploitation field Gradusa. These are vibrations and noise, which may have an adverse impact on the habitats of bats. Cavers and experts on bats have also been included in the process of selecting the micro-location.